Non-equilibrium universality in the dynamics of dissipative cold atomic gases - Marcuzzi, Matteo; Levi, Emanuele; Li, Weibin; Garrahan, Juan P.; Olmos, Beatriz; Lesanovsky, Igor (IOP Publishing, 2015)
The theory of continuous phase transitions predicts the universal collective properties of a physical system near a critical point, which for instance manifest in characteristic power-law behaviours of physical observables. The well-established concept at or near equilibrium, universality, can also characterize the physics of systems out of equilibrium. The most fundamental instance of a genuine non-equilibrium phase transition is the directed percolation universality class, where a system switches from an absorbing inactive to a fluctuating active phase. Despite being known for several decades it has been challenging to find experimental systems that manifest this transition. Here we show theoretically that signatures of the directed percolation universality class can be observed in an atomic system with long range interactions. Moreover, we demonstrate that even mesoscopic ensembles — which are currently studied experimentally — are sufficient to observe traces of this non-equilibrium phase transition in one, two and three dimensions.